Study of the state of moisture in the curd paste with sumach extract and the addition of buckwheat groats - Kochubei-Lytvynenko, Oksana; Marynin, Andrii; Yushchenko, Natalya; Kuzmyk, Ulyana; Lazarenko, Maxim (Eastern-European Journal of Enterprise Technologies, 2017)
We investigated the state of moisture in the curd paste with sumach extract with added non-toasted buckwheat groats (buckwheat groats) using a method of differential-thermal analysis. The base for curd paste was soft dietary curd. 10 % of extract of the spice sumach on milk whey (5 % of extractive substances) and 25 % of a buckwheat-whey mixture were added to the acid-milk base. The content of the adsorption moisture in the buckwheat-whey mixture is higher compared with the soft dietary curd. The highest value of pre-exponential factor and activation energy of the buckwheat-whey mixture predetermines the capability of retaining free moisture and serve as the moisture-binding component. A comparative analysis was performed for the state of moisture in the curd paste with buckwheat groats, in the curd paste with a moisture-retaining component, modified starch (E 1410) (dosage is 1.3 %). The amount of adsorption moisture in the curd paste with buckwheat groats was 32 %, whereas the curd paste, stabilized by modified starch, contained 32.5 %, which proves the efficiency of using buckwheat groats as the moisture-binding component